2014
DOI: 10.2337/dc14-1203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HbA1c, Followed From Onset of Type 1 Diabetes, on the Development of Severe Retinopathy and Nephropathy: The VISS Study (Vascular Diabetic Complications in Southeast Sweden)

Abstract: OBJECTIVEHbA 1c is strongly related to the development of diabetes complications, but it is still controversial which HbA 1c level to strive for in the treatment of type 1 diabetes. The aim of the current study was to evaluate HbA 1c , followed from diagnosis, as a predictor of severe microvascular complications and to formulate HbA 1c target levels for treatment. RESEARCH DESIGN AND METHODSA longitudinal observation study followed an unselected population of 451 patients diagnosed with type 1 diabetes during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
85
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 38 publications
(26 reference statements)
10
85
1
6
Order By: Relevance
“…Vascular Diabetic Complications in Southeast Sweden (VISS) study reported similar findings [21]. The VISS study a longitudinal observational study of 451 patients with diabetes who were followed for up to 24 years found that keeping HBA1c below 7.6% was beneficial in preventing retinopathy and persistent microalbuminuria for up to 20 years [21]. Intensive blood pressure control in patients with type 2 diabetes reduced the incidence and progression of diabetic neuropathy over 4-5 years follow up similar to the results in our study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Vascular Diabetic Complications in Southeast Sweden (VISS) study reported similar findings [21]. The VISS study a longitudinal observational study of 451 patients with diabetes who were followed for up to 24 years found that keeping HBA1c below 7.6% was beneficial in preventing retinopathy and persistent microalbuminuria for up to 20 years [21]. Intensive blood pressure control in patients with type 2 diabetes reduced the incidence and progression of diabetic neuropathy over 4-5 years follow up similar to the results in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Hyperglycaemia and hypertension are the main risk factors of developing retinopathy in patients with diabetes as also seen with our study [20]. Vascular Diabetic Complications in Southeast Sweden (VISS) study reported similar findings [21]. The VISS study a longitudinal observational study of 451 patients with diabetes who were followed for up to 24 years found that keeping HBA1c below 7.6% was beneficial in preventing retinopathy and persistent microalbuminuria for up to 20 years [21].…”
Section: Discussionsupporting
confidence: 66%
“…Despite advances in insulin formulation and delivery, patients with type 1 diabetes often fail to reach the target HbA1c of <7% 1, 4. Inadequate glucose control can lead to acute conditions such as ketoacidosis 5, and to chronic complications including retinopathy, nephropathy and cardiovascular disease 6, 7, 8. Compared with the general population, the risk of cardiovascular disease is nearly eight times greater in patients with type 1 diabetes 7, and the increased risk of mortality from heart disease is even greater 9.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Nathan et al 20 valores de HbA1c acima de 10,4% estão associadas a um aumento de sete vezes o risco de morte devido a complicações cardiovasculares. Um estudo recente demonstrou que valores de HbA1c menores que 7,6% esta associada a uma prevenção do desenvolvimento de complicações microvasculares por no mínimo 20 anos 21 . Há uma correlação direta forte entre os níveis de glicose pré-exercício e pós-exercício (r=0,851, p=0,002).…”
Section: Discussionunclassified